Computed CD4 percentage as a low-cost method for determining pediatric antiretroviral treatment eligibility - Callens, Steven FJ (BioMed Central, 2008)
BACKGROUND: The performance of the WHO recommendations for pediatric antiretroviral treatment (ART) in resource poor settings is insufficiently documented in routine care. METHODS: We compared clinical and immunological criteria in 366 children aged 0 to 12 years in Kinshasa and evaluated a simple computation to estimate CD4 percent, based on CD4 count, total white blood cell count and percentage lymphocytes. Kappa (κ) statistic was used to evaluate eligibility criteria and linear regression to determine trends of CD4 percent, count and total lymphocyte count (TLC). RESULTS: Agreement between clinical and immunological eligibility criteria was poor (κ = 0.26). One third of children clinically eligible for ART were ineligible using immunological criteria; one third of children immunologically eligible were ineligible using clinical criteria. Among children presenting in WHO stage I or II, 54 (32%) were eligible according to immunological criteria. Agreement with CD4 percent was poor for TLC (κ = 0.04), fair for total CD4 count (κ = 0.39) and substantial for CD4 percent computational estimate (κ = 0.71). Among 5 to 12 years old children, total CD4 count was higher in younger age groups (-32 cells/mm(3 )per year older), CD4 percent was similar across age groups. CONCLUSION: Age-specific thresholds for CD4 percent optimally determine pediatric ART eligibility. The use of CD4 percent computational estimate may increase ART access in settings with limited access to CD4 percent assays.